1999
DOI: 10.1177/106591299905200201
|View full text |Cite
|
Sign up to set email alerts
|

Win, Lose, or Draw: Predicting the Outcome of Civil Wars

Abstract: a government victory, a rebel victory, or a negotiated settlement? To explore this question we present an expected utility model of the choice rebels and governments face between accepting a settlement or continuing to fight. The model implies that a settlement becomes more likely as (1) estimates of the probability of victory decline; (2) costs of conflict increase; (3) estimates of the time required to win increase; or (4) the utility from a settlement increases relative to that of victory.Factors that (1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 18 publications
(13 reference statements)
4
65
0
Order By: Relevance
“…In other words, the duration of conflict increases the likelihood of negotiated settlement. In the study by Mason, Fett, and Weingarten (Mason et al 1999), it is also reported that there is a curvilinear relationship: the square term of conflict duration is negatively associated with negotiated settlement. This is an indication that mediation is most likely to occur in the easiest conflict situation: those situations where negotiated settlements are also most likely to be reached.…”
Section: Resultsmentioning
confidence: 85%
“…In other words, the duration of conflict increases the likelihood of negotiated settlement. In the study by Mason, Fett, and Weingarten (Mason et al 1999), it is also reported that there is a curvilinear relationship: the square term of conflict duration is negatively associated with negotiated settlement. This is an indication that mediation is most likely to occur in the easiest conflict situation: those situations where negotiated settlements are also most likely to be reached.…”
Section: Resultsmentioning
confidence: 85%
“…These expectations have been confirmed empirically (Mason et al, 1999). The rebels' hope is to survive long enough to be able to build a force sufficient to defeat the government or force it to agree to a settlement.…”
Section: Outcome Of the Civil Warmentioning
confidence: 70%
“…Previous research has established that conflict duration is positively associated with the probability of the war ending in a negotiated settlement and negatively associated with the probability of both government victory and rebel victory (Mason and Fett, 1996;Mason et al, 1999;Fearon, 2004). The longer a civil war lasts, the more the protagonists are compelled to adjust their estimates of the probability of victory (P v ), the time required to achieve victory (t v ), and the accrued costs of achieving victory .…”
Section: Outcome Of the Civil Warmentioning
confidence: 96%
See 2 more Smart Citations